Determination of Sea Toll Performance, Analysis of Regional Economic Income, Investment, and Logistics Warehouses: Study Library Research - Alfais Amin Darmawan (Siber Nusantara of Economic and Finance Review, 2025)
This study aims to analyze the influence of regional economic income, investment, and logistics warehouses on the performance of sea tolls in Indonesia. Using a literature review approach, this study synthesizes findings from various relevant internationally indexed academic articles. The research method used is descriptive qualitative with a literature review approach. Data were collected from reputable international indexed articles obtained through databases such as Scopus, Web of Science, Emerald, Springer, and Google Scholar. The selected literature was analyzed using reduction techniques, data presentation in matrix form, and comparative synthesis to find patterns, similarities, and differences between studies. The results of the study indicate that regional economic income, investment, and logistics warehouses affect sea toll performance. The limitations of this study lie in its nature as a literature review-based, study, so that generalization of the results still requires support from empirical research with primary data. The contribution of this study is to provide an integrative conceptual framework regarding the role of regional economic income, investment, and logistics warehouses on sea toll performance.